2018
DOI: 10.1021/acs.orglett.7b03673
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Quinolines via Co(III)-Catalyzed and DMSO-Involved C–H Activation/Cyclization of Anilines with Alkynes

Abstract: A unique Co(III)-catalyzed and DMSO-involved C-H activation/cyclization of simple, cheap, and easily available anilines with alkynes for direct and highly efficient synthesis of privileged quinolines with exclusive regioselectivity and broad substrate/functional group tolerance and in good to excellent yields, where DMSO was employed as both the solvent and the C building block of quinoline products, is reported. Mechanistic experiments revealed that the versatile reaction might employ the 2-vinylbenzenamine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…For example, various indole and pyrrole derivatives could be easily prepared through Cp*Co(III)‐catalyzed [3+2] cyclization reactions (Scheme , path a) . Moreover, a series of quinolines were synthesized via a Cp*Co(III)‐catalyzed [3+2+1] C−H annulation of anilines with alkynes involving DMSO as the C1 building block (Scheme , path b) . Besides, several groups also achieved the construction of quinoline moieties and quinoline N ‐oxides through the formal [4+2] cyclization reactions (Scheme , path c) .…”
Section: Figurementioning
confidence: 99%
“…For example, various indole and pyrrole derivatives could be easily prepared through Cp*Co(III)‐catalyzed [3+2] cyclization reactions (Scheme , path a) . Moreover, a series of quinolines were synthesized via a Cp*Co(III)‐catalyzed [3+2+1] C−H annulation of anilines with alkynes involving DMSO as the C1 building block (Scheme , path b) . Besides, several groups also achieved the construction of quinoline moieties and quinoline N ‐oxides through the formal [4+2] cyclization reactions (Scheme , path c) .…”
Section: Figurementioning
confidence: 99%
“…Recently, Xu et al . (2018) has developed a novel cobalt catalyzed method for the synthesis of quinolines from anilines and alkynes involving DMSO as C1 source via C−H activation and cyclisation strategies (Scheme ) . Herein, K 2 S 2 O 8 is used for the activation of DMSO into active species.…”
Section: Reaction Solvents As Precursors For the Installation Of Key mentioning
confidence: 99%
“…Xu et al, demonstrated a Co(III)-catalyzed new approach for the synthesis quinolines (226) in which DMSO is involved via C-H activation/coupling of easily accessible anilines (35) with alkynes (225) (Scheme 84). 112 In this reaction, DMSO not only acts as a solvent but also as C 1 building block of the products. The added advantages of this procedure are the enhanced regioselectivity, use of non-toxic solvents and good to excellent yields.…”
Section: Various Approaches For the Synthesis Of Quinolines And Theirmentioning
confidence: 99%